2019
DOI: 10.1002/acm2.12655
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric study of the plan quality and dose to organs at risk on tangential breast treatments using the Halcyon linac

Abstract: Purpose To investigate the plan quality and doses to the heart, contralateral breast (CB), ipsilateral lung (IL), and contralateral lung (CL) in tangential breast treatments using the Halcyon linac with megavoltage setup fields. Methods Radiotherapy treatment plans with tangential beams from 25 breast cancer patients previously treated on a C‐arm linac were replanned for Halcyon. Thirteen corresponded to right‐sided breasts and 12 to left‐sided breasts, all with a dose prescription of 50 Gy in 25 fractions. Pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
30
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 28 publications
8
30
0
Order By: Relevance
“…Previous studies have demonstrated that Halcyon could reduce the treatment time signi cantly compared to conventional LINACs [3][4][5][6][7]. Our study proved the same results in radiotherapy for bilateral breast cancer.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Previous studies have demonstrated that Halcyon could reduce the treatment time signi cantly compared to conventional LINACs [3][4][5][6][7]. Our study proved the same results in radiotherapy for bilateral breast cancer.…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, we inferred that low-dose MV CBCT was the optimal setup-eld mode. Flores-Martinez et al [6] compared four different setup-eld plans for unilateral breast cancer, in their opinion low-dose MV CBCT was the most suitable technique for patients treated on Halcyon. The result was the same as ours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After its clinical introduction in 2017, the performance of the new radiotherapy delivery platform Halcyon (H, Varian Medical Systems, Palo Alto, USA) was investigated for a variety of different treatment indications [10][11][12][13][14][15][16][17][18][19][20]. In general, the potential performance equivalence between H and other carm delivery systems was proven for head and neck, breast, prostate [13] and brain tumours [15].…”
Section: Introductionmentioning
confidence: 99%
“…Conventional RT used tangential breast/chest wall and anterior axillary supraclavicular fields. 19 , 20 Additional multileaf collimator segments were allowed to optimize the planning, using the Pinnacle3 Station, collapsed cone convolution algorithm. For tomotherapy, we used the TomoTherapy treatment planning system (Hi-Art, Accuray Inc., Sunnyvale, CA) for inverse planning (dynamically penalized likelihood method-cost function).…”
Section: Methodsmentioning
confidence: 99%